“Antarctic on fire”: Paleo-wildfire events associated with volcanic deposits in the Antarctic Peninsula during the Late Cretaceous - Manfroi, Joseline; Trevisan, Cristine; Dutra, Tânia Lindner; Jasper, André; Carvalho, Marcelo De Araujo; Aquino, Francisco Eliseu; Leppe, Marcelo (Frontiers in Earth Science, 2023)
The occurrence of paleo-wildfire events during the Campanian age of the Late Cretaceous is demonstrated in this study for the first time with deposits from the King George Island, South Shetland Islands, Antarctic Peninsula. With the aim of providing information that fills important paleoenvironmental and paleobiogeographic gaps about the end of the Cretaceous for the Gondwana, samples of macroscopic charcoal were collected at two different volcanic levels of the Price Point outcrop, King George Island, during the expeditions to the Antarctic Peninsula by the Brazilian Antarctic Program (PROANTAR). The samples of charcoal were treated and later analyzed under a stereomicroscope and scanning electron microscope. The analysis allowed the identification of morphoanatomical structures with potential taxonomic affinity with Podocarpaceae. These conifers were important in temperate forests of high-latitude environments during the Late Cretaceous, and this is in accordance with previous palaeobotanical records from Price Point. The analysis also showed that southern paleofloras were subject to the occurrence of paleo-wildfires much more frequently than previously thought. This indicates that fire and active volcanism were significant modifiers of the ecological niches of austral floras, because even in distal areas, the source of ignition for forest fires often came from contact with a hot volcanic ash cloud, where the vegetation was either totally or partially consumed by fire.